Real-time tracking of source movement by Cherenkov emission imaging for high-dose-rate brachytherapy. (1st July 2022) - Yogo, K.; Tatsuno, Y.; Shimo, T.; Noguchi, Y.; Okudaira, K.; Nozawa, M.; Ishiyama, H.; Yasuda, H.; Oguchi, H.; Yamamoto, S.
Abstract: Quality assurance (QA) of the source movement is essential for ensuring the safe delivery of high-dose-rate (HDR) brachytherapy. Here, we proposed a simple and effective method for real-time tracking of the source movement in high-dose-rate brachytherapy based on Cherenkov emission imaging. The Cherenkov light emitted from water irradiated by 192 Ir-source γ-rays was captured using a high-sensitivity video camera. The source positions and dwell intervals were determined from the light images and compared with the preset values. The source dwell times and transit speeds were measured from the time course of the source positions. The brightness profiles were compared with the dose distributions provided by the treatment planning system. The source movements were visualized in real time as a movie of Cherenkov light emissions. The source positional intervals measured from the Cherenkov emission images agreed well to the preset values within 0.3 mm. The source dwell times were comparable to the preset values within 0.2 s, and the transit speeds were similar to those of previous reports. The brightness distributions agreed with the dose distributions within approximately 40%, except near the source center. The proposed Cherenkov method has good potential for tracking the source movement in real time in brachytherapy, as it could enable simultaneous measurements of the source positions, dwell times, and dose distributions.